Contributions to the measurement and management of intellectual capital: an accounting perspective - Pires, Rui A.R. (2011)
Intellectual capital (IC) represents a set of strategic assets, with an intangible nature, which contributes to the creation of competitive advantages and sustainable value, therefore should be identified, measure managed and published by organizations.